The Effect of Four Lateral Methyl Groups on The Thermotropic Behavior of Azo Liquid Crystal Homologous Series - Latif, I. K.; Hassan, E.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Twenty binary liquid crystalline mixture diagrams were investigated with polarizing microscope and differential scanning calorimeter (DSC). Four binary mixture diagrams were constructed to identify the smectic phase which is found to be the same in all components of the homologous series (4-n-alkoxy -2, 3, 5, 6-tetra methyl-4-n-alkoxy azo benzene) (nPA4M). The fifth binary mixture diagram was between the (6PA4M) and the reference liquid crystal compound, terephthlylidene-bis (4-n-butylanaline) (TBAA) to identify the type of smectic mesophase of these compounds, and the results obtained were compared with the literature. To study the effect of the 4 methyl lateral groups on the thermotropic behavior of the (nPA4M) homologous series, fifteen binary mixture diagrams were divided in to three parts, each part contains five diagrams. The first binary diagrams were (nPA4M) with reference liquid crystalline compound 4-n-hexyloxyphenyl-4-n`-hexyloxy azobenzene (HPA) (compound without lateral group). The second five diagrams were between (nPA4M) and reference liquid crystal compound 4-butylpheny-4-[(4-ethyloxyphenyl)carbonyl]oxy-3-methyl benzoate (4B2M) ( compound with one methyl lateral group), and the last part of binary diagrams was between (nPA4M) and reference liquid crystal compound 4-butyl-2methylpheny4-[(4ethyloxyphenyl) carbonyl]oxy-3-methylbenzoate(4B2,3M) ( compound has two methyl lateral groups). .